Improving Students' Mathematical Disposition with the Knowledge Sharing Learning Strategy - Ita Handayani; Widyah Noviana; Weni Gurita Aedi (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kristen Indonesia, 2026)
Applied graph is a compulsory course in the Pamulang Informatics Engineering study program. Applied graph is a course that teaches the concepts, algorithms, and practical applications of graph theory. Graph theory itself is a branch of discrete mathematics that studies network structures consisting of nodes (vertices) connected by edges (arcs). Although the applied graph course is an important course to study, some students still consider it difficult to understand. The purpose of this study was to determine whether there was a difference in the mathematical disposition of students who were given treatment using the knowledge sharing strategy and students who were given treatment using the expository strategy. The research method used was a quantitative method with a quasi-experimental design. The sample used in this study consisted of 59 students. Data collection was carried out using a mathematical disposition questionnaire. The instrument was tested for validity on 136 students, with 29 valid statements, and for reliability using Cronbach's alpha coefficient 0.992. The analysis technique used an independent t-test with a p-value of 0.005. The results of this study indicate that there is a difference in the mathematical disposition of students who were given the knowledge sharing strategy and students who were given the expository strategy.